Improved growth control of atomically thin WSe2 flakes using pre-deposited W source - Nguyen, Van Tu; Phan, Ngoc Minh; Park, Ji Yong (Journal of Materials Science: Materials in Electronics, 2021)
The improvement in the growth yield and control of atomically thin WSe2 flakes by chemical vapor deposition (CVD) using pre-deposited WO3 nanopowders as a W source is demonstrated. WO3 nanopowders are pre-deposited on the growth substrate and utilized as a W source instead of separate W sources in the CVD system. In this way, mostly mono or bilayer WSe2 flakes are grown on the growth substrate with high density and an average size of around 20 μm. The devices based on the as-grown WSe2 flakes show p-type behaviors with a high on/off ratio of ~ 105 and carrier mobility of ~ 0.5 cm2V− 1 s−1 as well as a large positive photoresponse. The density and size of WSe2 flakes can be controlled by adjusting the amount of pre-deposited WO3 nanopowders. This approach can be used to grow W-based two-dimensional materials as well as their heterostructures with other materials such as graphene and carbon nanotubes.
Keywords: As-grown; Average size; Bi-layer; Chemical vapour deposition; Growth control; Growth substrates; Growth yield; Nano powders; P-type behaviors; Vapor deposition systems